Research trends in post-stroke aphasia (2004–2024): a bibliometric and visualized analysis - Peng, Yufeng; Peng, Kewei; Ying, Yunfeng; Li, Luyao (Frontiers in Neurology, 2025)
IntroductionThis study employs bibliometric analysis to systematically investigate the evolutionary trajectory and disciplinary dynamics of post-stroke aphasia mechanism research from 2004 to 2024.MethodsThrough multidimensional examination of 3,492 publications from Web of Science Core Collection.ResultsWe identify paradigm shifts characterized by three distinct phases: initial reliance on neuroimaging for anatomical localization of language-area lesions, subsequent focus on white matter remodeling and neuromodulation techniques validating neural plasticity hypotheses, and recent advances in functional connectomics integrated with multimodal intervention strategies. International collaboration exhibits marked geographic disparities, with the United States, United Kingdom, and Australia forming the knowledge-production nucleus through leadership in neuromodulation innovation and brain network research. While China ranks among top contributors in publication volume, it confronts dual challenges of insufficient transnational cooperation and underdeveloped culturally-adapted assessment tools. Notably, a persistent technology-practice gap persists as a critical bottleneck - despite neuroimaging’s dominance in mechanistic studies, clinical integration of functional assessment tools remains suboptimal, and neuromodulation trials demonstrate attenuated effect sizes compared to preclinical models. Temporal analysis reveals research imbalance favoring acute-phase intervention studies over chronic-phase management research. Emerging technologies such as digital therapeutics exhibit limited research clustering.DiscussionBased on these findings, we propose a multidimensional framework integrating precision neuromodulation, cross-cycle rehabilitation pathways, and digital ecosystems, prioritizing multicenter brain network database development and dialect-adaptive assessment scales. This investigation provides empirical mapping of current research landscapes and actionable insights for future investigations in post-stroke aphasia rehabilitation.